2020
DOI: 10.1038/s41419-020-2591-0
|View full text |Cite
|
Sign up to set email alerts
|

Correction of the tumor suppressor Salvador homolog-1 deficiency in tumors by lycorine as a new strategy in lung cancer therapy

Abstract: Salvador homolog-1 (SAV1) is a tumor suppressor required for activation of the tumor-suppressive Hippo pathway and inhibition of tumorigenesis. SAV1 is defective in several cancer types. SAV1 deficiency in cells promotes tumorigenesis and cancer metastasis, and is closely associated with poor prognosis for cancer patients. However, investigation of therapeutic strategies to target SAV1 deficiency in cancer is lacking. Here we found that the small molecule lycorine notably increased SAV1 levels in lung cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Numerous studies have explored the anti-tumor activity of LYC, including against cancers such as colorectal, gastric, bladder, lung, breast, melanoma, multiple myeloma, osteosarcoma, and hematological malignancies. The molecular mechanism of the anti-tumor activity of LYC is mainly attributed to the selective induction of apoptosis in cancer cells [13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have explored the anti-tumor activity of LYC, including against cancers such as colorectal, gastric, bladder, lung, breast, melanoma, multiple myeloma, osteosarcoma, and hematological malignancies. The molecular mechanism of the anti-tumor activity of LYC is mainly attributed to the selective induction of apoptosis in cancer cells [13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Lycorine (LYC), one component of Amaryllidaceae, is an alkaloid that displays various beneficial functions in some disease models, including anti-inflammation, anti-fibrosis, antiviral, anti-aging, and anti-tumor effects [8][9][10][11][12]. Recently, numerous studies focused on investigating the antitumor feature of LYC in colorectal cancer, gastric cancer, bladder cancer, lung cancer, breast cancer, melanoma, multiple myeloma, osteosarcoma, hematological malignancies [13][14][15][16][17][18][19][20][21]. After administration of LYC, cancer cells died selectively in large numbers because of apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we found that Ly has a wide range of anti-tumor activities including apoptosis, autophagy, proliferation and so on [36][37][38]. In this study, we intend to compare whether DS-Ly NPs has better anti-tumor effects than Ly.…”
Section: Discussionmentioning
confidence: 96%
“…Lycorine inhibits the growth and metastasis of various types of cancers, such as non-small cell lung cancer (Li et al, 2019), glioblastoma multiforme (Shen et al, 2018), lung cancer (Zhao et al, 2020), gastric cancer (Li et al, 2020). The previous review has testi ed that lycorine inhibited the growth and metastasis of breast cancer cells by inhibition of protein biosynthesis and the STAT3 and the Src/FAK signaling pathway (Wang et al, 2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%